(untitled) (World Bulletin of Management and Law, 2022)
The contribution of total quality management (TQM) is extremely valuable for organizations to overcome inside and outside challenges. The aim of this study to understand the impact of quality management on firm performance. Through conducting a case study of Hamoud Boualam Company, the findings show there is a positive impact of quality management on firm performance. Limitations and recommendations for future studies are provided.